How the PDGF receptor induces cell proliferation - Kazlauskas, Andrius (Henry Stewart Talks, 2007)
How is signaling linked to cell cycle events?, Recent findings that growth factors trigger multiple waves of signaling, Engaging the cell cycle program by late wave signalling, The hypothesis that growth factors trigger at least two distinct phases of signaling, and that each of them makes a unique contribution to cell cycle progression, Appreciation of how growth factor-induced signaling drives the cell out of quiescence and commits it to one round of the cell cycle
Archived at 2018/05/31